Public Health Policies to combat Covid-19 in the Unified Health System: Integrative literature review (Research, Society and Development, 2024)
The Ministry of Health (MS) defines Covid-19 as an acute respiratory infection caused by the Severe Acute Respiratory Syndrome coronavirus (SARS-CoV-2), of high transmissibility and global distribution. This integrative review aimed to reflect on the challenges and strategies for implementing public policies to combat Covid-19 in Brazil. The search for bibliographic references was carried out on the VHL (Virtual Health Library) platforms; LILACS (Latin American and Caribbean Literature on Health Sciences); PUBMED from NIH (National Library of Medicine) and SCIELO (Scientific Electronic Library Online). 753 articles were found, of which 20 were selected for the study, and grouped into 05 categories: Public Policies to combat Covid-19 in the SUS; Covid-19 in Brazil and social distancing measures; Primary Health Care in the Covid-19 scenario; Hospital Care in the pandemic; and SUS Financing. The review indicated the essentiality of building strategies to provide quality care to patients affected by Covid-19, whether in PHC or in Hospital Care. This directly involves the three spheres of management, considering the need to overcome several mishaps encountered during the fight against the pandemic in Brazil. In addition to the low investments to finance public health policies in the SUS.